Toward Specialized or Integrated Systems in Northwest Europe: On-Farm Eco-Efficiency of Dairy Farming in Germany - Reinsch, Thorsten; Loza, Cecilia; Malisch, Carsten Stefan; Vogeler, Iris; Kluß, Christof; Loges, Ralf; Taube, Friedhelm (Frontiers in Sustainable Food Systems, 2021)
Intensive confinement (IC) systems for dairying have become widespread during the last decades. However, potential advantages of alternative systems such as full-grazing (FG) or integrated dairy / cash-crop (IFG) systems with regards to better provision of ecosystem services are widely discussed. To investigate performance and environmental impacts, we compared four prevailing dairy systems using an on-farm research study. The farm types differed in their share of pasture access and quantity of resource inputs: (i) an IC with a high import of supplements and mineral fertilizers; (ii) a semi-confinement (SC) with daytime pasture access during summer and moderate import of supplementary feeds representing the base-line scenario; (iii) a FG based on grazed seeded grass-clover swards with no purchased N-fertilizers and low quantities of supplementary feeds; and (iv) an IFG comparable to FG but based on grass-clover leys integrated in a cash-crop rotation. Results revealed highest milk productivity (16 t energy-corrected-milk (ECM) ha-1) and farm-N-balance (230 kg N ha-1) in IC; however, the highest product carbon footprint (PCF; 1.2 CO2eq kg ECM-1) and highest N-footprint (13 g N kg ECM-1) were found in the baseline system SC. The FG and IFG revealed on average similar forage dry matter yields (10-11 t DM ha-1) at similar crude protein and net-energy-lactation ratios per kg DM-intake compared to the IC and SC. The PCF in FG were comparable to IC (0.9 vs. 1.1 kg CO2eq kg ECM-1) but at a lower N-footprint (9 vs. 12 g N kg ECM-1). However, despite low measured N-losses in the FG system, the farm-N-surplus was exceeded by 90 kg N ha-1. A further reduction was only possible in the IFG (50 kg N ha-1) by accounting for a potential N-carry-over from N-rich plant residues to the cash-crop unit, leading to the lowest PCF (0.6 kg CO2eq kg ECM-1) for the IFG, with still moderate milk yield levels ( 10 500 kg ECM ha-1). According to this bottom-up approach based on field data, improved integrated grazing systems could provide an important opportunity to increase the ecosystem services from dairy farming, operating with land use efficiencies similar to IC.